Transient hypoxemia induced by cortical electrical stimulation: A mapping study in 75 patients. (2nd June 2020) - Loizon, Marine; Ryvlin, Philippe; Chatard, Benoit; Jung, Julien; Bouet, Romain; Guenot, Marc; Mazzola, Laure; Bezin, Laurent; Rheims, Sylvain
Abstract : Objective: To identify which cortical regions are associated with direct electrical stimulation (DES)–induced alteration of breathing significant enough to impair pulse oximetry (SpO2 ). Methods: Evolution of SpO2 after 1, 352 DES was analyzed in 75 patients with refractory focal epilepsy who underwent stereo-EEG recordings. For each DES, we assessed the change in SpO2 from 30 seconds prior to DES onset to 120 seconds following the end of the DES. The primary outcome was occurrence of stimulation-induced transient hypoxemia as defined by decrease of SpO2 ≥5% within 60 seconds after stimulation onset as compared to pre-DES SpO2 or SpO2 nadir <90% during at least 5 seconds. Localization of the stimulated contacts was defined according to MarsAtlas brain parcellation and Freesurfer segmentation. Results: A stimulation-induced transient hypoxemia was observed after 16 DES (1.2%) in 10 patients (13%), including 6 in whom SpO2 nadir was <90%. Among these 16 DES, 7 (44%) were localized within the perisylvian cortex. After correction for individual effects and the varying number of DES contributed by each person, significant decrease of SpO2 was significantly associated with the localization of DES ( p = 0.019). Conclusion: Though rare, a significant decrease of SpO2 could be elicited by cortical direct electrical stimulation outside the temporo-limbic structures, most commonly after stimulation of the perisylvian cortex.